Eco-friendly management of Pyricularia oryzae - The causal agent of blast of paddy - Fathima2*, S.L. Sukanya1,2, D. Yamini2 and S. K. (Current Botany, 2011)
Integrated management of Pyricularia oryzae by eco-friendly approaches is promising. In this study we isolated and tested the essential oils and oleoresin from Piper nigrum, Coriander sativum and Curcuma domestica for their effect on Pyricularia oryzae in rice. These were evaluated for their antifungal activity againstÃ‚Â P. oryzae in vitro by poison food technique. Seed health testing was performed using the standard blotter method. We isolated P. oryzae and cultured on potato dextrose agar (PDA) medium to maintain pure culture for our future experiments. The pure culture of P. oryzae was tested against different concentration of essential oils and oleoresin on PDA medium. Incubated for several days and plates were checked for mycelial growth inhibition and percentages of inhibitions were calculated. Maximum inhibition of mycelial growth was observed in pepper oil which showed 5.9%, 5.5%, 4.4% and 7.0% of inhibition at 100ppm, 200ppm, 300ppm and control, respectively. Mycelial growth was completely inhibited at 500ppm and 1000ppm concentration. This indicated that pepper oil is most effective against P. oryzae pathogen. Oleoresin and coriander oil is less effective. The results of the current study indicated that each of the three essential oils tested, reduced the natural infection frequency in P. oryzae.